2013
DOI: 10.1261/rna.036400.112
|View full text |Cite
|
Sign up to set email alerts
|

piRNA dynamics in divergent zebrafish strains reveal long-lasting maternal influence on zygotic piRNA profiles

Abstract: Transposable elements (TEs) are mobile genetic elements that can have many deleterious effects on the fitness of their host. The germline-specific PIWI pathway guards the genome against TEs, deriving its specificity from sequence complementarity between PIWI-bound small RNAs (piRNAs) and the TEs. The piRNAs are derived from so-called piRNA clusters. Recent studies have demonstrated that the piRNA repertoire can be adjusted to accommodate recent TE invasions by capturing invading TEs in piRNA loci. Thus far, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Analysis of piRNA populations in zebrafish hybrids show evidence for maternal effects on the ratio of sense and antisense piRNAs in the progeny (Kaaij et al, 2013). Despite similarities between the fly and zebrafish piRNA pathways, including presence of a pingpong loop and observed fertility phenotypes (Houwing et al, 2007(Houwing et al, , 2008, further investigation will be needed to determine the extent of inheritance in this system.…”
Section: Pirna Functions Beyond Transposon Silencingmentioning
confidence: 99%
“…Analysis of piRNA populations in zebrafish hybrids show evidence for maternal effects on the ratio of sense and antisense piRNAs in the progeny (Kaaij et al, 2013). Despite similarities between the fly and zebrafish piRNA pathways, including presence of a pingpong loop and observed fertility phenotypes (Houwing et al, 2007(Houwing et al, , 2008, further investigation will be needed to determine the extent of inheritance in this system.…”
Section: Pirna Functions Beyond Transposon Silencingmentioning
confidence: 99%
“…Indeed, there was significantly higher piRNA expression from PERLs, and this phenomenon was consistently found in piRNA populations across development ( Figure 6E). Interestingly, PERLs were also enriched significantly for retro-transposons, which are the major piRNA targets in zebrafish (Houwing et al, 2007;Kaaij et al, 2013), but not DNA transposons ( Figure 6F and G). Given that DNA transposons cover a significantly larger fraction of the genome than retro-elements (Howe et al, 2013) this could indicate that retro-elements play a role in driving PERL expression.…”
Section: Perls Are Transposon-rich Pirna Producing Locimentioning
confidence: 99%
“…We described before that piRNAs, in particular those that are Ziwi-bound, are maternally provided to zebrafish embryos and can influence piRNA characteristics trans-generationally (Houwing et al, 2007;Kaaij et al, 2013). However, due to experimental difficulties in manipulating this maternal piRNA pool, the function of the maternal piRNAs in zebrafish is still unclear.…”
Section: Pirna Pathway Activation In Zebrafish Pgcsmentioning
confidence: 99%
“…Long-term piRNA inheritance appears to be well conserved: recently it was shown that piRNAs are inherited for 50 generations in Drosophila [40], and for at least two generations in Danio rerio [44]. While piRNAs are involved in many inherited immunity effects, they are obviously not central to all such mechanisms.…”
Section: Inherited Protection Against Transposonsmentioning
confidence: 99%